2022
DOI: 10.3390/healthcare10081417
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Human Development Index and Confirmed COVID-19 Cases by Country

Abstract: It is important to understand the ultimate control of COVID-19 in all countries around the world in relation to the characteristics of developed countries, LDCs, and the variety of transmission characteristics of COVID-19. Therefore, this study aimed to identify factors associated with confirmed cases of COVID-19 with a focus on the Human Development Index (HDI). The units of analysis used for the current study were countries, and dataset were aggregated from multiple sources. This study used COVID-19 data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
12
2
1
Order By: Relevance
“…Furthermore, in some Latin-American countries, it has been estimated that at least 20-40% of the case fatality rate depends on the HDI 10 . Across countries, countries with high HDI prevented more COVID-19 deaths, con rmed that the most signi cant fraction of their cases and deaths were due to COVID-19, and even had higher recovery rates 11,12 . However, contrary to expected, within Peru and during the deathliest COVID-19 waves, those districts with higher HDI had higher death counts.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, in some Latin-American countries, it has been estimated that at least 20-40% of the case fatality rate depends on the HDI 10 . Across countries, countries with high HDI prevented more COVID-19 deaths, con rmed that the most signi cant fraction of their cases and deaths were due to COVID-19, and even had higher recovery rates 11,12 . However, contrary to expected, within Peru and during the deathliest COVID-19 waves, those districts with higher HDI had higher death counts.…”
Section: Discussionmentioning
confidence: 90%
“…There are several types of research in the literature about the association between HDI and confirmed COVID-19 cases by country. The hierarchical multiple linear regression models are presented in [35] to identify factors associated with confirmed cases of COVID-19 with a focus on the HDI. Countries with a high HDI could conduct more tests per person, leading to more confirmed cases than those with a low HDI.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that the global COVID-19 epidemic can be predicted by considering macro variables such as population size, the Human Development Index (HDI), and migration rate. Infectious diseases and respiratory infections have higher mortality rates in countries with lower HDIs (Heo et al, 2022 ; Mirahmadizadeh et al, 2022 ). However, a study in Italy found that HDI was directly related to both infection rates and COVID-19 mortality rates (Fabiani et al, 2021 ).…”
Section: Literaturementioning
confidence: 99%